Potential Recurrence of Odontogenic Keratocyst Post-Surgery, Rapid Review - Widyandhika, Cindy Widyandhika Ayu; Anggraini, Jamas Ari; Yusuf, Harmas Yazid (Journal of Syiah Kuala Dentistry Society, 2023)
Background: Odontogenic keratocyst is one of the most frequent cysts found in the jaw. Odontogenic keratocyst, or OKC, is a benign but locally aggressive cyst with a higher recurrence rate than other odontogenic cysts after surgical treatment. The OKC recurrence rate is reported to be around 2.5% to 62.5%. Objective: This rapid review analyzes the most frequent recurrence potential factors after surgical procedures. Material and Methods: Articles search by using a combination of the keywords "odontogenic keratocyst" "keratocystic odontogenic tumor," "potential," "probability," "recur," "relapse, "recurrence" in three databases; PubMed, ScienceDirect, and Google Scholar. Article inclusion criteria include articles that have data on the recurrence of odontogenic keratocyst after surgical treatment; in the English language; issued within the last 10 years (2012-2022); and using observational research with all types of study designs (cohort, cross-sectional, and case-control). This study used the PRISMA protocol (Preferred Reporting Items for Systematic Review and Meta-Analysis). Results: Thirteen articles with an observational study design were included in this rapid review, consisting of thirteen articles with retrospective cohort design. This study recorded two hundred fifty-three cases of recurrence out of 1263 cases of OKC, with a mean follow-up period of 53.6 months. Recurrences were found more often in male patients than female patients (1.58:1), especially in the third and fourth decades of age. The multilocular form of the lesion (n = 52), especially on the mandible, was more common than the unilocular form of the lesion (n = 83). Teeth preserved in the sites of involvement caused incomplete cyst removal and increased the risk of recurrence. Conclusion: This rapid review showed that the percentage of potential OKC recurrences ranged from 7.1% to 45%, with an average recurrence rate of 22.5%. The presence of a daughter or satellite cyst and residual teeth or teeth preserved in the lesion area that was not removed in the form of a large multilocular cyst affects the potential for recurrence.